Formulasi body scrub alami berbahan sari labu kuning dan ampas kelapa sebagai eksfolian - Maria Irwani; Wurul Maghfiranda; Amelia Sari; Ernita Silviana; Burdah Burdah (Poltekkes Kemenkes Aceh, 2024)
Background: Pumpkin juice and coconut pulp are natural ingredients that have potential as body scrubs. Pumpkin is known to be rich in antioxidants, such as vitamin C, vitamin E, and β-carotene, which play an important role in protecting the skin from UV damage. Coconut pulp functions as a natural exfoliant that can remove dead skin cells, scrape off the outermost layer of dry and rough skin, and moisturize the skin. The use of these natural ingredients in making body scrubs aims to develop skin care products made from natural ingredients.Objective: This study aims to formulate pumpkin juice (Curcubita moschata) and coconut pulp (Cocos nucifera L.) into a body scrub preparation and evaluate the physical characteristics of the preparation.Methods: Experimental research was conducted at the Unsyiah Herbarium Laboratory and the Pharmaceutics Laboratory of the Poltekkes Kemenkes Aceh from February to April 2023. Evaluation of the preparation includes organoleptic test, homogeneity, spreadability, emulsion type, irritation, liking test, and pH measurement. Data analysis was carried out descriptively.Results: The results showed that the formulated body scrub preparation had a semi-solid shape, yellow color, distinctive aroma of pumpkin juice and coconut pulp, and good homogeneity. The pH of the preparation was in accordance with SNI standards (pH 6.1-6.2), the spreadability met the requirements (5.5 cm), and the type of emulsion formed was oil in water. All preparations did not cause skin irritation, and the formula most preferred by respondents was F3 (20% pumpkin juice and 15% coconut pulp).Conclusion: The combination of pumpkin juice and coconut pulp can be used as a natural exfoliant in body scrub cream.